Reuse of silongs in ancestral houses in Pila, Laguna - Antonio, Angeli C.; Faustino, Johanna Victoria A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT In the year 2000, 30 ancestral houses in Pila, Laguna were declared to be part of a National Historical Landmark. In such houses, the term silong was used to refer to the ground storey which was traditionally a storage area for crops, furniture and processional carriages. Nowadays, silongs are being used as additional living areas, and even commercial and retail spaces. This qualitative study aimed to find out if, why and how silongs in ancestral houses in Pila, Laguna have been reused. The researcher used purposive sampling to select 3 homeowners to participate in interviews. A photo-documentation of the façades was done, and a survey of the past and present uses of the silongs of all remaining ancestral houses that the National Historical Grounded theory was used as the theoretical framework of the study. Open coding and axial coding were used in the data analysis. The results of the study revealed that most ancestral houses in Pila have had their silongs repurposed, and that a majority are being used as commercial, retail and/or office spaces. It was found that the Agrarian Reform in 1972 (Presidential Decree No. 27) indirectly led to the stop of the use of silongs as storage areas for crops. The reuse of such a big space in the house was inevitable. It was revealed that the factors that led to the reuse of silongs include economics, lifestyle and space requirements. However, it was found that proper adaptive reuse theory was not fully implemented in the reuse of the spaces as is required by law for structures of historical and cultural value (National Cultural Heritage Act of 2009).
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Architecture, Domestic -- Philippines -- Laguna